USE OF INFOGRAPHIC MEDIA IN FORMING LEARNING INTEREST AND CREATIVITY OF MADRASAH STUDENTS - Muhammad hasbullah Ridwan; Risma Ulyatul Izza (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This study aims to describe the use of infographic learning media in fostering creativity and learning interest among tenth-grade students at Madrasah. The background of this study is based on the lack of variation in learning media in the classroom, which has an impact on the low level of students’ learning interest and creativity, particularly in Indonesian language learning. Infographic media were chosen as an alternative learning medium because of their advantages in presenting material visually, concisely, and attractively, which are expected to increase students’ engagement in learning. This study employed a descriptive qualitative approach with tenth-grade students of Madrasah as the research subjects. Data were collected through observation, interviews, and documentation. Data validity was ensured through technique triangulation and source triangulation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the use of infographic media has a positive impact on students’ learning interest and creativity. Students became more enthusiastic, active, and focused during the learning process. The visual, colorful, and systematic presentation of materials was able to attract students’ attention and reduce learning boredom. In addition, students’ creativity developed through activities of creating simple infographics and engaging in active classroom discussions. Therefore, infographic learning media can be concluded to be effective in fostering students’ learning interest and creativity and can serve as an innovative alternative learning medium in Indonesian language learning at the Madrasah level.